ANALISIS PEMANFAATAN DAN VALIDASI HOTSPOT VIIRS NIGHTFIRE UNTUK IDENTIFIKASI KEBAKARAN HUTAN DAN LAHAN DI INDONESIA - Zubaidah, Any; Vetrita, Yenni; Priyatna, M.; Ayu D., Kusumaning (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2015)
Suomi National Polar-Orbiting Partnership (Suomi NPP) that was launched on 28 October 2011 was a new generation of weather satellites of NASA. It has been continuing to develop algorithms for environmental monitoring applications including fire hotspot which is a global product. Therefore, an evaluation for the specific region is necessary. This paper is aimed to validate the VIIRS Nightfire (VNF) in Indonesia, particularly in Riau Province. MODIS fire hotspot (MOD 14) nighttime was used as well as a comparison. Statistical analysis was performed to calculate the precise location of hotspots at 1 and 2 km radius buffering of the detected fire. A field survey and SPOT 5 imagery which has a higher spatial resolution. Accuracy was calculated from them all the hotspots were detected in a period of 3 weeks which is adapted to the availability of SPOT 5 imagery, by considering the analysis of single and dissolve buffering. The result shows that VNF has an average accuracy rate of 84.31%. This result can be compared with the analysis of the MODIS hotspots product. Thus, VNF was very significant to be used along with MODIS hotspots, in particular for monitoring land/ forest fires at night.